2005
DOI: 10.1080/13651500510029129
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric symptoms and diagnoses in thyroid disorders: a cross-sectional study

Abstract: Objective Endocrine dysfunction may produce symptoms that are difficult to distinguish from the clinical manifestations of psychiatric disorders. In particular, the function of the hypothalamic-pituitary-thyroidal axis is known to be associated with a number of psychiatric abnormalities, such as depression and anxiety. In this study, we tested the hypothesis that depression is more commonly encountered in hypothyroidism, while anxiety is more prevalent in hyperthyroidism. Additionally, we aimed to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Six studies involved community-dwelling healthy individuals [12, 17, 20, 21, 23, 29] while the remaining nine single-centre studies recruited out-patients who were investigated for suspected SCH [7, 1316, 19, 22, 24, 30]. Eight studies reported the mean depression scores between individuals with SCH and healthy controls, of which five used HDRS [12, 13, 15, 16, 22] and three used BDI [17, 23, 24]. All other studies used different but validated scales to diagnose depression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies involved community-dwelling healthy individuals [12, 17, 20, 21, 23, 29] while the remaining nine single-centre studies recruited out-patients who were investigated for suspected SCH [7, 1316, 19, 22, 24, 30]. Eight studies reported the mean depression scores between individuals with SCH and healthy controls, of which five used HDRS [12, 13, 15, 16, 22] and three used BDI [17, 23, 24]. All other studies used different but validated scales to diagnose depression.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies showed higher depression scores among patients with SCH than control group [12, 16, 2224]. Five other studies showed no difference in the number of individuals with depression between SCH and control group [8, 15, 20, 21, 30], whereas three found no difference in the depression scores [13, 15, 17]. However, pooled analysis showed that individuals with SCH had higher risk of depression compared with euthyroid controls (relative risk 2.36, 95% CI 1.84 to 3.02; p < 0.001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2008). Psychiatric implications of thyroid dysfunction primarily involve depression and anxiety (Aslan et al. 2005).…”
Section: Other Medical Issuesmentioning
confidence: 99%
“…In Asian countries, about 15% (n=9) out of the 60 thyroid disorder patients suffered from depression in Nepal (3). Besides 24.3% (n=19) out of 80 thyroid disorder patients has been diagnosed as depression in Turkey (4) . Based on these study findings, depression can found in patient with abnormal thyroid function.…”
Section: Introductionmentioning
confidence: 99%
“…However, the association between the thyroid hormone and depression still debatable. Eventhough there were conflicting on association between the thyroid hormone and depression, but some studies showed that there were an association between the imbalance of thyroid hormone and depression (4,9). In conrast, a population-based study found that there were International Journal of Care Scholars 2021;4 (1) no significant association between TSH level and depression by using Beck Depressive Inventory-II (BDI-II) in Germany (2).…”
Section: Introductionmentioning
confidence: 99%